THE CONSTRUCTION OF STRIKE'S SOCIAL CONCEPT A PIAGETIAN EVOLUTIONARY STUDY - Giachetto Saravali, Eliane [UNESP]; Pereira Mano, Amanda de Mottos; Guimaraes, Taislene; Pall Oriani, Angelica; Morandi Rotoli, Liliane Ubeda [UNESP] (Univ Estadual Campinas, Fac Educacao, 2020)
From the Piagetian studies on social knowledge construction, this article presents the data of a qualitative and quantitative research, whose objective was to investigate the understanding of the strike notion in public and private students, aged between 6 and 21 years. The research with transversal trajectory design consisted of 80 participants, distributed as follows: 20 subjects aged 6 years, 20 subjects aged 11 years, 20 subjects aged 16 years and 20 subjects aged 21 years. Still, for each age group, there was division as to the origin of the school institution, thus, 10 participants were from public institutions and 10, from private institutions. The instrument used was a clinical-critical interview that dealt with the notion of strike. The interviews were analyzed according to the levels of social reality understanding, through the construction of sub-levels, plus analytical statistics of correlation between variables. In general, it was found that students' ideas focused on the sub-level IIa, revealing an understanding of a little elaborate strike notion, based on more personal judgments and apparent aspects. Statistical analysis showed no difference in the answers according to the schools in which the participants were enrolled. Relevant aspects about the construction of social knowledge are discussed.
Keywords: Strike; Social knowledge; Piagetian theory